Alteration of Thyroid-Related Hormones within Normal Ranges and Early Functional Outcomes in Patients with Acute Ischemic Stroke - Xiao-yan Xu; Wen-yu Li; Xing-yue Hu (International Journal of Endocrinology)
This study evaluated the prognostic value of thyroid-related hormones within normal ranges after acute ischemic stroke. This was a retrospective study and we reviewed 1072 ischemic stroke patients consecutively admitted within 72 h after symptom onset. Total triiodothyronine (T3), total thyroxine (T4), free T3, free T4, and thyroid-stimulating hormone (TSH) were assessed to determine their values for predicting functional outcome at the first follow-up clinic visits, which usually occurred 2 to 4 weeks after discharge from the hospital. 722 patients were finally included. On univariate analysis, poor functional outcome was associated with presence of atrial fibrillation as the index event. Furthermore, score of National Institutes of Health Stroke Scale (NIHSS), total T4, free T4, and C-reactive protein at admission were significantly higher in patients with poor functional outcome, whereas free T3 and total T3 were significantly lower. On multiple logistic regression analysis, lower total T3 concentrations remained independently associated with poor functional outcome [odds ratio (OR), 0.10; 95% confidence interval (CI), 0.01–0.84; P=0.035]. The only other variables independently associated with poor functional outcome were NIHSS scores. In sum, lower total T3 concentrations that were within the normal ranges were independently associated with poor short-term outcomes.